Answer:
I cannot see the screen. Write it out please and I will answer.
Step-by-step explanation:
Answer:
x = 8
Step-by-step explanation:
All the sides are equal. So, it is an equilateral triangle. So, all angles are 60 each
6x + 12 = 60
6x = 60 - 12
6x = 48
x = 48/6
x = 8
Answer:
A. −4 + 4 = 0
Step-by-step explanation:
-4 + 4 = 0
4 - 4 = 0
So option A will be the answer
Answer:
Step-by-step explanation:
Given: The triangle with coordinate A(4,6), B(2,-2) and C(-2,-4). D is the mid point of AB and E is the mid point of AC.
To prove: DE is parallel to BC.
Construction: Join DE.
Proof: If we prove the basic proportionality theorem that is
, then it proves that DE is parallel to BC.
Now, Mid Point D has coordinates=
and Mid Point E has coordinates=![(\frac{4-2}{2},\frac{6-4}{2})=(1,1)](https://tex.z-dn.net/?f=%28%5Cfrac%7B4-2%7D%7B2%7D%2C%5Cfrac%7B6-4%7D%7B2%7D%29%3D%281%2C1%29)
Now, AD= ![\sqrt{(4-3)^{2}+(6-2)^{2}}=\sqrt{17}](https://tex.z-dn.net/?f=%5Csqrt%7B%284-3%29%5E%7B2%7D%2B%286-2%29%5E%7B2%7D%7D%3D%5Csqrt%7B17%7D)
DB=![\sqrt{(3-2)^{2}+(2+2)^{2}}=\sqrt{17}](https://tex.z-dn.net/?f=%5Csqrt%7B%283-2%29%5E%7B2%7D%2B%282%2B2%29%5E%7B2%7D%7D%3D%5Csqrt%7B17%7D)
AE=![\sqrt{(4-1)^{2}+(6-1)^{2}}=\sqrt{34}](https://tex.z-dn.net/?f=%5Csqrt%7B%284-1%29%5E%7B2%7D%2B%286-1%29%5E%7B2%7D%7D%3D%5Csqrt%7B34%7D)
EC=![\sqrt{(1+2)^{2}+(1+4)^{2}}=\sqrt{34}](https://tex.z-dn.net/?f=%5Csqrt%7B%281%2B2%29%5E%7B2%7D%2B%281%2B4%29%5E%7B2%7D%7D%3D%5Csqrt%7B34%7D)
Now, ![\frac{AD}{DB}=\frac{AE}{EC}](https://tex.z-dn.net/?f=%5Cfrac%7BAD%7D%7BDB%7D%3D%5Cfrac%7BAE%7D%7BEC%7D)
=![\frac{\sqrt{17}}{\sqrt{17}}=\frac{\sqrt{34}}{\sqrt{34}}=\frac{1}{1}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B17%7D%7D%7B%5Csqrt%7B17%7D%7D%3D%5Cfrac%7B%5Csqrt%7B34%7D%7D%7B%5Csqrt%7B34%7D%7D%3D%5Cfrac%7B1%7D%7B1%7D)
Hence, ![\frac{AD}{DB}=\frac{AE}{EC}](https://tex.z-dn.net/?f=%5Cfrac%7BAD%7D%7BDB%7D%3D%5Cfrac%7BAE%7D%7BEC%7D)
Thus, By basic proportionality theorem, DE is parallel to BC.